Barriers and motivations for women in technology: Study with students from IF Sertão Pernambucano based on an extension experience (Research, Society and Development, 2025)
This study investigated the factors that contribute to the low female representation in the field of Information Technology (IT). The objective of this research is to understand the factors that contribute to the existence of a reduced number of women in computing and to build hypotheses that explain this problem, analyzing the sociocultural aspects that influence women's choice, entry, and retention in the field. The research was based on the extension project Clube da Programação, developed at IF Sertão-PE, Campus Floresta, which promotes actions to expand youth access and interest in programming. Within the Clube da Programação, a nucleus called Programeninas: Breaking Barriers and Building Futures stands out, focusing on encouraging female participation in technology through specific activities. The study combined a literature review and the application of a structured questionnaire to 47 students from the Integrated High School in Informatics and the course in Information Technology Management, with analysis guided by the stages of Design Thinking. The results indicated that despite the high interest and family support expressed by the participants, the students still face gender stereotypes, discomfort in predominantly male environments, and a lack of female role models. It is concluded that inclusive institutional policies, mentoring programs, and visibility initiatives, such as those promoted by the Clube da Programação and its Programeninas nucleus, are essential to reduce the gender disparity in the technology sector.